A Comprehensive Systematic Review of the Association Between Vitamin D Deficiency and Alopecia Areata - Salsabilla Gina Rania; Nanda Khirana Bangsawan Puteri (Jurnal Sehat Indonesia (JUSINDO), 2026)
Alopecia areata (AA) is a non-scarring hair loss disorder commonly considered an autoimmune condition in which the immune system attacks the hair follicle during the anagen phase. Vitamin D is a fat-soluble hormone primarily known for regulating calcium homeostasis via the vitamin D receptor (VDR), which is expressed in various cells including immune cells and hair follicles. This systematic review aims to examine the association between vitamin D deficiency and alopecia areata. The study followed the PRISMA 2020 guidelines. A literature search was conducted using databases including PubMed, SagePub, and ScienceDirect for articles published between 2014 and 2024. Review articles, duplicates, and incomplete studies were excluded. Results: From 1,751 initially identified articles, only eight studies met the inclusion criteria after a three-step screening process. All eight full-text articles were analyzed in depth. Vitamin D levels demonstrate an inverse relationship with the severity, extent, and pattern of alopecia areata. Thus, vitamin D deficiency may serve as a contributing factor in the pathogenesis of AA or may exacerbate the existing condition.